An intelligent machine condition monitoring model for servo systems - AKÜNER, MUSTAFA CANER; AKGÜN, GAZİ (My University, 2022)
The installation of industrial servo systems and the determination of control parameters are limited to the skills and knowledge of the commissioner. In addition, commissioned systems are often not re-optimized if environmental influences or loads change. The goal of this research is to create an artificial neural network (ANN) model for servo systems that will keep the servo system's proportional, integral, and derivative (PID) parameters working optimally. For this process, a machine condition monitoring algorithm developed with the ANN technique, which uses the data such as actual current, torque, power, position to be obtained from the servo system on an industrial controller, for the control and rearrangement of the parameters.
Keywords: Servo System; Artificial Neural Network; PLC; ProfiNET